2010
DOI: 10.1177/1933719109352687
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pomegranate Seed Extract and β-Sitosterol on Rat Uterine Contractions

Abstract: The aim of this study was to investigate the effects of pomegranate (Punica granatum L., Punicaceae) seed extract on uterine contractility. Pomegranate seeds were methanolic extracted and their constituents analyzed using gas chromatography and mass spectrometry. Isometric force was measured in strips of longitudinal rat myometrium and the effects of pomegranate seed extract studied. We found beta-sitosterol to be the main constituent of the extract (16%) and its effects were also investigated. Pomegranate see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 29 publications
4
25
0
2
Order By: Relevance
“…This could be similar to the contraction induced by wild ginger (Costus speciosus) rhizome [47] and pomegranate (Punica granatum L., Punicaceae) seed [48] extracts which was also shown to solely depend on the extracellular Ca 2+ . In this study, FDA binding to the muscarinic, oxytocin and PGF2α receptors may trigger the extracellular Ca 2+ influx prior to contraction.…”
Section: Discussionsupporting
confidence: 54%
“…This could be similar to the contraction induced by wild ginger (Costus speciosus) rhizome [47] and pomegranate (Punica granatum L., Punicaceae) seed [48] extracts which was also shown to solely depend on the extracellular Ca 2+ . In this study, FDA binding to the muscarinic, oxytocin and PGF2α receptors may trigger the extracellular Ca 2+ influx prior to contraction.…”
Section: Discussionsupporting
confidence: 54%
“…It is suggested that the extract is a potent phasic activity stimulator in rat uterus, which happens due to the non-estrogenic effects of beta-sitosterol on inhibiting sarco-endoplasmic reticulum Ca 2+ -ATPase (SERCA) and K channel, which resulted in contraction by calcium entry on L-type calcium channels and myosin light chain kinase (MLCK). [58] It is demonstrated that pomegranate fruit extract has an embryonic protective nature against adrianycin-induced oxidative stress (adrianycin is a chemotherapeutic drug used in cancer treatment). [59] Moreover, pomegranate juice consumption could increase epididymal sperm concentration, motility, spermatogenic cell density, diameter of seminiferous tubules and germinal cell layer thickness.…”
Section: Chemical Compositionmentioning
confidence: 99%
“…Phytosterols have also attracted attention as inhibitors of sarcoplasmic reticulum calcium ATPase and potassium ion channels [4,5]. As part of a collaboration investigating the structural influences on uptake and processing of sterol esters[6], we required semipreparative amounts of β-sitosterol.…”
Section: Introductionmentioning
confidence: 99%